IMPLEMENTATION OF THE CONCEPT OF CRIME PREVENTION THROUGH ENVIRONMENT DESIGN (CPTED) IN IMPROVING SECURITY AND ORDER IN CLASS IIA PEKALONGAN PRISON - Putra, Yulizar; Simanjuntak, Meitisa Vanya (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study was to analyze the application of the Crime Prevention Through Environment Design (CPTED) concept in improving security and order in Class IIA Pekalongan Prison. To analyze the obstacles faced by Class IIA Pekalongan Prison in implementing the Crime Prevention Through Environment Design (CPTED) concept. Qualitative research methods. Data were collected through direct observation, interviews with security officers, and analysis of related documents. The results of the study The application of the CPTED concept carried out by Class IIA Pekalongan Prison in an effort to prevent prisoner violations includes 6 (six) aspects as follows: a) The territoriality aspect is considered good, namely a sterile area from violations. b) The surveillance aspect still has ineffectiveness in installing CCTV. c) Access control has been implemented properly, such as dividing the level of areas that the general public may pass through. d) Target hardening has been carried out with several efforts, such as placing officers at the available guard posts. e) Image and management aspects: Pekalongan Class IIA Prison has provided efforts to maintain prison buildings, especially the area where prisoners live. f) Activity support to divert the focus of treatment of violations of the rules of procedure Pekalongan Class IIA Prison offers a wide range of activities. The obstacles that are the weaknesses of the CPTED concept that is applied, such as the quality and quantity of human resources, the available budget, and also the less favorable geographical location. Keywords: Crime Prevention; Environmental Design; Security; Order